Preparation method of non-metallic sulfur and nitrogen doped porous carbon nanosheet and application thereof in synthesis of nitrile from aldehyde
By preparing non-metallic sulfur and nitrogen-doped porous carbon nanosheet catalysts, the problems of high temperature and high pressure and the use of precious metals in existing aldehyde-to-nitrile synthesis methods have been solved, realizing an efficient, green and sustainable aldehyde-to-nitrile synthesis process that is suitable for industrial production.
Patent Information
- Application Number
- CN202410745116.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-11
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2044-06-11
AI Technical Summary
Existing methods for synthesizing nitriles from aldehydes suffer from high temperature and pressure, use of precious metals and organic solvents, resulting in high economic costs, and lack of efficient, green and sustainable catalysts.
Non-metallic sulfur and nitrogen-doped porous carbon nanosheet catalysts were prepared by ball milling and high-temperature pyrolysis of chitosan, sodium lignin sulfonate, and potassium hydroxide. These catalysts were used for the oxidative cyanidation reaction of aldehydes, avoiding the use of cyanides and precious metals. Nitriles were synthesized in a one-step process under mild conditions using ammonia as the nitrogen source.
It achieves high conversion and high selectivity in the synthesis of nitriles. The catalyst has metal-free properties, does not leach active substances, is heterogeneous, and has good tolerance. It is suitable for industrial production and has green sustainability and economic benefits.
Smart Images

Figure CN118663298B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of energy and chemical engineering, specifically to a method for preparing non-metallic sulfur-nitrogen-doped porous carbon nanosheets and their application in the synthesis of nitrile from aldehydes. Background Technology
[0002] Nitriles are highly useful compounds and have been widely used as multifunctional intermediates in the production of pesticides, pharmaceuticals, dyes, fine chemicals, and functional materials. Generally, nitriles can be synthesized via several methods involving cyanides, but the high toxicity of cyanides significantly limits their application. Therefore, cyanide-free strategies and several cyanonitrile-free synthesis methods have been developed, including amine oxidation, amide or azide oxidation; dehydration synthesis of amides / oximes; amine oxidation of aromatics; direct reaction of organohalides with sodium azide; and direct oxidation of alcohols or aldehydes. Among these cyanide-free methods, the direct oxidative cyanidation of aldehydes using ammonia as the nitrogen resource is a particularly attractive route because aldehydes can be obtained in large quantities from renewable biomass resources, while ammonia is an inexpensive and widely available nitrogen resource. Furthermore, the direct oxidative cyanidation of aldehydes avoids the use and pre-synthesis of cyanides / special nitrogen resources.
[0003] Chinese patent CN202111447045.X discloses a method for preparing a supported cobalt-based catalyst using benzyl alcohol compounds as raw materials for one-step direct oxidative cyanidation: Benzyl alcohol compounds are added to a reaction vessel, with one of ammonia, ammonium bicarbonate, and urea as the ammonia source, a certain amount of oxygen is introduced, the reaction temperature is controlled at 100–130℃, the reaction time is 5–12 h, and the reaction vessel pressure is 1.0–3.0 MPa. This method involves high reaction temperatures and high oxygen pressures, and uses relatively expensive cobalt metal, which will increase economic costs. Chinese patent CN201810519102.2 discloses a method for synthesizing p-toluene using p-xylene as a raw material: 20 mL of p-dimethylbenzene is placed in a reaction vessel, which is heated to 130–135 °C. DMF solvent, catalyst, and co-catalyst are added sequentially, with the oxygen flow rate controlled at 900 mL / min and the hydrogen flow rate at 100 mL / min. The reaction is allowed to proceed for 4–5 hours. The reaction solution is then cooled to room temperature, and the resulting transparent, colorless crystals are p-toluene. The crystals are washed 2–3 times with DMF, and the DMF is removed by filtration. This method requires the use of organic solvents such as p-xylene and DMF, and necessitates a continuous flow of oxygen and hydrogen, which increases economic costs. Summary of the Invention
[0004] To overcome the problems of existing technologies, this invention provides a method for preparing a metal-free sulfur-nitrogen co-doped porous carbon nanosheet catalyst for the synthesis of nitriles from aldehydes, and a method for one-step oxidation of benzaldehyde cyanide and its derivatives to synthesize nitriles using ammonia as a nitrogen source. This invention uses chitosan, sodium lignin sulfonate, and potassium hydroxide, mixed by a simple ball milling method, followed by high-temperature pyrolysis under an argon atmosphere to prepare the catalyst. This catalyst can catalyze the one-pot synthesis of nitriles from aldehydes with high conversion and high selectivity under mild conditions. In addition to its metal-free properties, this catalyst also exhibits characteristics such as no leaching of active materials, heterogeneity, no further conversion of the formed nitriles, and good tolerance to other oxidizable groups. The catalyst has great potential, and this inexpensive and efficient catalyst is expected to be widely used in industrial production in the future.
[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0006] The first aspect of this invention provides a method for preparing non-metallic sulfur-nitrogen-doped porous carbon nanosheets, comprising the following steps:
[0007] Sodium lignosulfonate, chitosan, and potassium hydroxide were mixed and ball-milled. The powder was then placed in a tube furnace for pyrolysis. After pyrolysis, the powder was soaked in acetonitrile and centrifuged. The resulting solid was washed with deionized water and dried to obtain the non-metallic sulfur-nitrogen-doped porous carbon nanosheets.
[0008] Preferably, the mass ratio of sodium lignosulfonate, chitosan, and potassium hydroxide is (4-1):(2-1):1; more preferably, the mass ratio of sodium lignosulfonate, chitosan, and potassium hydroxide is (2-3):(2-1):1.
[0009] Preferably, the ball mill rotates at a speed of 300-600 rpm, and the milling time is 8-24 hours. The ball milling method used in this invention is intermittent ball milling with both forward and reverse rotations. Specifically, the intermittent ball milling is performed with a 5-minute pause after every 30 minutes of milling.
[0010] Preferably, the pyrolysis conditions are: under an inert gas atmosphere, a heating rate of 4-6℃ / min, a pyrolysis temperature of 600-900℃, a holding time of 60-90min, and finally natural cooling; more preferably, the pyrolysis temperature is 700-900℃.
[0011] In some specific embodiments of the present invention, the pyrolyzed powder is soaked in acetonitrile for 5-15 minutes, and then centrifuged at a speed of 8000-12000 rpm for 4-6 minutes.
[0012] Preferably, the drying is vacuum drying, and the vacuum drying temperature is 60-80℃ for 10-14 hours.
[0013] The second aspect of the present invention provides a non-metallic sulfur-nitrogen-doped porous carbon nanosheet, which is obtained by the preparation method of the non-metallic sulfur-nitrogen-doped porous carbon nanosheet.
[0014] The third aspect of this invention provides the application of the aforementioned non-metallic sulfur-nitrogen-doped porous carbon nanosheets in the synthesis of nitrile from aldehydes.
[0015] A fourth aspect of this invention provides a method for synthesizing nitrile from aldehydes, using the aforementioned non-metallic sulfur-nitrogen-doped porous carbon nanosheets as a catalyst, comprising the following steps:
[0016] Aldehyde compounds and catalysts are added to a reaction vessel, acetonitrile is added as a solvent, and ammonia is added. Oxygen is first introduced to purge the air from the reaction vessel, and then a certain amount of oxygen is introduced. The reaction is carried out at 70-100℃ for 6-10 hours to obtain nitrile compounds.
[0017] Preferably, the aldehyde compound includes at least one selected from benzaldehyde, 4-methylbenzaldehyde, 4-ethylbenzaldehyde, 4-hydroxybenzaldehyde, 4-fluorobenzaldehyde, 4-bromobenzaldehyde, 4-chlorobenzaldehyde, 4-nitrobenzaldehyde, 4-methoxybenzaldehyde, 4-isopropylbenzaldehyde, 4-ethoxybenzaldehyde, and 3-hydroxybenzaldehyde.
[0018] Preferably, the mass-to-volume ratio of the aldehyde compound to ammonia is 1 g : (0.05-0.5) mL. The concentration of the ammonia in this invention is 25-30 wt%.
[0019] Preferably, the oxygen flow rate is such that the final pressure inside the reactor after oxygen introduction is 0.5-1 MPa. The oxygen used in this invention is high-purity oxygen with a purity of 99.99%.
[0020] Compared with the prior art, the beneficial effects of the present invention are:
[0021] This invention provides a method for preparing a metal-free sulfur-nitrogen co-doped porous carbon nanosheet catalyst for the synthesis of nitriles from aldehydes, and a method for one-step oxidation of benzaldehyde cyanide and its derivatives to nitriles using ammonia as a nitrogen source. The catalyst prepared by this invention exhibits high activity, enabling a one-pot catalytic synthesis of nitriles from aldehydes with high conversion and high selectivity under mild conditions. In addition to its metal-free properties, this catalyst also exhibits characteristics such as non-leaching of the active material, heterogeneity, no further conversion of the formed nitriles, and good tolerance to other oxidizable groups, demonstrating its great potential. This inexpensive and efficient catalyst is expected to be widely used in industrial production in the future.
[0022] Furthermore, this invention enhances the catalytic activity of carbon materials through the synergistic co-doping of non-metallic elements S and N, regulates active sites, enhances the electronic regulation capability of graphite nitrogen, and significantly improves the catalytic activity of oxidative nitrification of benzaldehyde derivatives to generate the corresponding nitrile.
[0023] Furthermore, this reaction uses ammonia as a nitrogen source and oxygen as an oxidant, and the synthetic route avoids the use of cyanide and the pre-synthesis of special nitrogen sources, greatly improving the green sustainability of the catalytic reaction.
[0024] Furthermore, the catalyst can be reused after the reaction, and its recovery can be achieved through simple operations: centrifugation, washing, and drying.
[0025] Furthermore, this invention employs a one-pot direct reaction of aldehydes and ammonia under oxygen conditions to prepare nitriles. In the reaction system, only benzonitrile and trace amounts of the intermediate imine were detected as products; no benzamide was formed, and no further oxidation occurred, indicating that the catalyst has high selectivity for this reaction.
[0026] Furthermore, the catalyst is very simple to prepare, the raw materials are renewable, and the preparation cycle is short. It has the advantages of being economical, green, efficient, and low-cost, and is expected to be applied in large-scale industrial production. Attached Figure Description
[0027] Figure 1 TEM image of SN-cns-900 in Example 1;
[0028] Figure 2 XRD patterns of the catalysts synthesized at different calcination temperatures in Examples 1-4;
[0029] Figure 3 The images show the Raman spectra of the catalysts synthesized at different calcination temperatures in Examples 1-4.
[0030] Figure 4 This is a pore size distribution diagram of the SN-cns-900 in Example 1;
[0031] Figure 5 The nitrogen adsorption-desorption curve of SN-cns-900 in Example 1;
[0032] Figure 6 The yield of benzonitrile in sulfur-nitrogen co-doped porous carbon nanosheets at different calcination temperatures;
[0033] Figure 7 The yield of benzonitrile with different amounts of ammonia water;
[0034] Figure 8 Benzonitrile yield of sulfur-nitrogen co-doped porous carbon nanosheets with different raw material ratios;
[0035] Figure 9 The yields of benzonitrile under different oxygen pressures;
[0036] Figure 10 The yield of benzonitrile is given at different ball milling speeds. Detailed Implementation
[0037] The specific embodiments of the present invention will be further described below. It should be noted that these descriptions are for the purpose of aiding understanding the present invention, but do not constitute a limitation thereof. Furthermore, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0038] Unless otherwise specified, the experimental methods used in the following embodiments are conventional methods, and the experimental materials used in the following embodiments are all available through conventional commercial channels.
[0039] Example 1
[0040] Weigh out 4.5316g of sodium lignosulfonate, 3.0425g of chitosan, and 1.5027g of potassium hydroxide and mix them in a planetary ball mill (the planetary ball mill speed is 300rpm, and the ball milling is carried out intermittently in both forward and reverse directions for 12 hours. The interval between forward and reverse rotation is 5 minutes after every 30 minutes of ball milling). Collect the powder after ball milling.
[0041] The ball-milled powder was placed in a ceramic crucible, which was then placed in a tube furnace. Argon gas was introduced, and a heating program was set for pyrolysis (heating rate 5℃ / min, pyrolysis temperature 900℃, holding time 90min, followed by natural cooling). After the temperature dropped to room temperature, the pyrolyzed black powder was collected and placed in centrifuge tubes. Acetonitrile was added to the centrifuge tubes for soaking, followed by centrifugation. This soaking and centrifugation process was repeated three times. The resulting solid was washed with deionized water until neutral and then vacuum dried at 80℃ for 12h to obtain sulfur-nitrogen co-doped porous carbon nanosheets, named SN-cns-900.
[0042] The prepared catalyst was subjected to benzaldehyde oxidation-cyanation reaction. 0.5238 g benzaldehyde, 50 mg SN-cns-900, 200 μL ammonia water and 0.8 MPa oxygen were added to a 25 mL reaction vessel and reacted under magnetic stirring at a temperature of 80 °C for 8 h to obtain benzonitrile with a yield of 95.9%.
[0043] Example 2
[0044] Weigh out 4.5038g of sodium lignosulfonate, 3.1134g of chitosan, and 1.4987g of potassium hydroxide and mix them in a planetary ball mill (the planetary ball mill speed is 300rpm, and the ball milling is carried out intermittently in both forward and reverse directions for 12 hours. The intermittent direction is: pause for 5 minutes after every 30 minutes of ball milling), and collect the powder after ball milling.
[0045] The ball-milled powder was placed in a ceramic crucible, which was then placed in a tube furnace. Argon gas was introduced, and a heating program was set for pyrolysis (heating rate of 5℃ / min, pyrolysis temperature of 800℃, holding time of 90min, followed by natural cooling). After the temperature dropped to room temperature, the pyrolyzed black powder was collected and placed in centrifuge tubes. Acetonitrile was added to the centrifuge tubes for soaking, followed by centrifugation. This soaking and centrifugation process was repeated three times. The resulting solid was washed with deionized water until neutral and then vacuum-dried at 80℃ for 12h to obtain sulfur-nitrogen co-doped porous carbon nanosheets, which were named SN-cns-800.
[0046] The prepared catalyst was subjected to benzaldehyde oxidation-cyanation reaction. 0.5199 g benzaldehyde, 50 mg SN-cns-800, 200 μL ammonia water and 0.8 MPa oxygen were added to a 25 mL reaction vessel and reacted under magnetic stirring at a temperature of 80 °C for 8 h, yielding benzonitrile with a yield of 85.7%.
[0047] Example 3
[0048] Weigh out 4.5235g of sodium lignosulfonate, 3.0403g of chitosan, and 1.5117g of potassium hydroxide and mix them in a planetary ball mill (the planetary ball mill speed is 300rpm, and the ball milling is carried out intermittently in both forward and reverse directions for 12 hours. The intermittent direction is: pause for 5 minutes after every 30 minutes of ball milling), and collect the powder after ball milling.
[0049] The ball-milled powder was placed in a ceramic crucible, which was then placed in a tube furnace. Argon gas was introduced, and a heating program was set for pyrolysis (heating rate of 5℃ / min, pyrolysis temperature of 700℃, holding time of 90min, followed by natural cooling). After the temperature dropped to room temperature, the pyrolyzed black powder was collected and placed in centrifuge tubes. Acetonitrile was added to the centrifuge tubes for soaking, followed by centrifugation. This soaking and centrifugation process was repeated three times. The resulting solid was washed with deionized water until neutral and then vacuum dried at 80℃ for 12h to obtain sulfur-nitrogen co-doped porous carbon nanosheets, which were named SN-cns-700.
[0050] The prepared catalyst was subjected to benzaldehyde oxidation-cyanation reaction. 0.5248 g benzaldehyde, 50 mg SN-cns-700, 200 μL ammonia water and 0.8 MPa oxygen were added to a 25 mL reaction vessel and reacted under magnetic stirring at a temperature of 80 °C for 8 h, yielding benzonitrile with a yield of 67.6%.
[0051] Example 4
[0052] Weigh out 4.5088g of sodium lignosulfonate, 3.0044g of chitosan, and 1.5087g of potassium hydroxide and mix them in a planetary ball mill (the planetary ball mill speed is 300rpm, and the ball milling is carried out intermittently in both forward and reverse directions for 12 hours. The intermittent direction is: pause for 5 minutes after every 30 minutes of ball milling), and collect the powder after ball milling.
[0053] The ball-milled powder was placed in a ceramic crucible, which was then placed in a tube furnace. Argon gas was introduced, and a heating program was set for pyrolysis (heating rate 5℃ / min, pyrolysis temperature 600℃, holding time 90min, followed by natural cooling). After the temperature dropped to room temperature, the pyrolyzed black powder was collected and placed in a centrifuge tube. Acetonitrile was added to the centrifuge tube for soaking, followed by centrifugation. This soaking and centrifugation process was repeated three times. The resulting solid was washed with deionized water until neutral and then vacuum dried at 80℃ for 12h to obtain sulfur-nitrogen co-doped porous carbon nanosheets, named SN-cns-600.
[0054] The BET surface areas of the catalysts synthesized at different calcination temperatures in Examples 1-4 are shown in Table 1 below:
[0055] Table 1
[0056] Group catalyst <![CDATA[BET specific surface area (m 2 / g)]]> 1 SN-cns-600 96 2 SN-cns-700 193 3 SN-cns-800 435 4 SN-cns-900 634
[0057] The elemental contents of S, C, H, and N of the catalysts synthesized at different calcination temperatures in Examples 1-4 are shown in Table 2 below:
[0058] Table 2
[0059]
[0060]
[0061] The catalyst prepared in Example 4 was subjected to benzaldehyde oxidative cyanation reaction. 0.5233 g benzaldehyde, 50 mg SN-cns-600, 200 μL ammonia water and 0.8 MPa oxygen were added to a 25 mL reaction vessel and reacted under magnetic stirring at a temperature of 80 °C for 8 h. The yield of benzonitrile was 0% (no reaction occurred).
[0062] The results of Examples 1-4 are shown in Table 3 and Appendix 4 below. Figure 6 As shown:
[0063] Table 3
[0064] Catalyst (calcination temperature) Reaction temperature / °C Oxygen pressure / MPa Reaction time / h Ammonia dosage / μL Benzonitrile yield / % SN-cns-900 80 0.8 8 200 95.9 SN-cns-800 80 0.8 8 200 85.7 SN-cns-700 80 0.8 8 200 67.6 SN-cns-600 80 0.8 8 200 -
[0065] Example 5
[0066] Weigh out 4.5316g of sodium lignosulfonate, 3.0425g of chitosan, and 1.5027g of potassium hydroxide and mix them in a planetary ball mill (the planetary ball mill speed is 300rpm, and the ball milling is carried out intermittently in both forward and reverse directions for 12 hours. The interval between forward and reverse rotation is 5 minutes after every 30 minutes of ball milling). Collect the powder after ball milling.
[0067] The ball-milled powder was placed in a ceramic crucible, which was then placed in a tube furnace. Argon gas was introduced, and a heating program was set for pyrolysis (heating rate 5℃ / min, pyrolysis temperature 900℃, holding time 90min, followed by natural cooling). After the temperature dropped to room temperature, the pyrolyzed black powder was collected and placed in centrifuge tubes. Acetonitrile was added to the centrifuge tubes for soaking, followed by centrifugation. This soaking and centrifugation process was repeated three times. The resulting solid was washed with deionized water until neutral and then vacuum dried at 80℃ for 12h to obtain sulfur-nitrogen co-doped porous carbon nanosheets, named SN-cns-900.
[0068] The prepared catalyst was subjected to benzaldehyde oxidation-cyanation reaction. 0.5198 g benzaldehyde, 50 mg SN-cns-900, 150 μL ammonia water and 0.8 MPa oxygen were added to a 25 mL reaction vessel and reacted under magnetic stirring at a temperature of 80 °C for 8 h, yielding benzonitrile with a yield of 92.8%.
[0069] Example 6
[0070] Weigh out 4.5316g of sodium lignosulfonate, 3.0425g of chitosan, and 1.5027g of potassium hydroxide and mix them in a planetary ball mill (the planetary ball mill speed is 300rpm, and the ball milling is carried out intermittently in both forward and reverse directions for 12 hours. The interval between forward and reverse rotation is 5 minutes after every 30 minutes of ball milling). Collect the powder after ball milling.
[0071] The ball-milled powder was placed in a ceramic crucible, which was then placed in a tube furnace. Argon gas was introduced, and a heating program was set for pyrolysis (heating rate 5℃ / min, pyrolysis temperature 900℃, holding time 90min, followed by natural cooling). After the temperature dropped to room temperature, the pyrolyzed black powder was collected and placed in centrifuge tubes. Acetonitrile was added to the centrifuge tubes for soaking, followed by centrifugation. This soaking and centrifugation process was repeated three times. The resulting solid was washed with deionized water until neutral and then vacuum dried at 80℃ for 12h to obtain sulfur-nitrogen co-doped porous carbon nanosheets, named SN-cns-900.
[0072] The prepared catalyst was subjected to benzaldehyde oxidative cyanation reaction. 0.5224 g benzaldehyde, 50 mg SN-cns-900, 100 μL ammonia water and 0.8 MPa oxygen were added to a 25 mL reaction vessel and reacted under magnetic stirring at a temperature of 80 °C for 8 h, yielding benzonitrile with a yield of 85.2%.
[0073] Example 7
[0074] Weigh out 4.5316g of sodium lignosulfonate, 3.0425g of chitosan, and 1.5027g of potassium hydroxide and mix them in a planetary ball mill (the planetary ball mill speed is 300rpm, and the ball milling is carried out intermittently in both forward and reverse directions for 12 hours. The interval between forward and reverse rotation is 5 minutes after every 30 minutes of ball milling). Collect the powder after ball milling.
[0075] The ball-milled powder was placed in a ceramic crucible, which was then placed in a tube furnace. Argon gas was introduced, and a heating program was set for pyrolysis (heating rate 5℃ / min, pyrolysis temperature 900℃, holding time 90min, followed by natural cooling). After the temperature dropped to room temperature, the pyrolyzed black powder was collected and placed in centrifuge tubes. Acetonitrile was added to the centrifuge tubes for soaking, followed by centrifugation. This soaking and centrifugation process was repeated three times. The resulting solid was washed with deionized water until neutral and then vacuum dried at 80℃ for 12h to obtain sulfur-nitrogen co-doped porous carbon nanosheets, named SN-cns-900.
[0076] The prepared catalyst was subjected to benzaldehyde oxidation-cyanation reaction. 0.5447 g benzaldehyde, 50 mg SN-cns-900, 50 μL ammonia water and 0.8 MPa oxygen were added to a 25 mL reaction vessel and reacted under magnetic stirring at a temperature of 80 °C for 8 h, yielding benzonitrile with a yield of 77.7%.
[0077] The results of Examples 1 and 5-7 are shown in Table 4 and Appendix 5 below. Figure 7 As shown:
[0078] Table 4
[0079] Catalyst (calcination temperature) Reaction temperature / ℃ Oxygen pressure / MPa Reaction time / h Ammonia dosage / μL Benzonitrile yield / % SN-cns-900 80 0.8 8 200 95.9 SN-cns-900 80 0.8 8 150 92.8 SN-cns-900 80 0.8 8 100 85.2 SN-cns-900 80 0.8 8 50 77.7
[0080] Example 8
[0081] Weigh out 3.0787g of sodium lignosulfonate, 3.0057g of chitosan, and 1.5027g of potassium hydroxide and mix them in a planetary ball mill (the planetary ball mill speed is 300rpm, and the ball milling is carried out intermittently in both forward and reverse directions for 12 hours. The intermittent direction is: pause for 5 minutes after every 30 minutes of ball milling), and collect the powder after ball milling.
[0082] The ball-milled powder was placed in a ceramic crucible, which was then placed in a tube furnace. Argon gas was introduced, and a heating program was set for pyrolysis (heating rate 5℃ / min, pyrolysis temperature 900℃, holding time 90min, followed by natural cooling). After the temperature dropped to room temperature, the pyrolyzed black powder was collected and placed in centrifuge tubes. Acetonitrile was added to the centrifuge tubes for soaking, followed by centrifugation. This soaking and centrifugation process was repeated three times. The resulting solid was washed with deionized water until neutral and then vacuum dried at 80℃ for 12h to obtain sulfur-nitrogen co-doped porous carbon nanosheets, named SN-cns-900.
[0083] The prepared catalyst was subjected to benzaldehyde oxidation-cyanation reaction. 0.5198 g benzaldehyde, 50 mg SN-cns-900, 200 μL ammonia water and 0.8 MPa oxygen were added to a 25 mL reaction vessel and reacted under magnetic stirring at a temperature of 80 °C for 8 h to obtain benzonitrile with a yield of 89.5%.
[0084] Example 9
[0085] Weigh out 1.5278g of sodium lignosulfonate, 1.5199g of chitosan, and 1.5221g of potassium hydroxide and mix them in a planetary ball mill (the planetary ball mill speed is 300rpm, and the ball milling is carried out intermittently in both forward and reverse directions for 12 hours. The intermittent direction is: pause for 5 minutes after every 30 minutes of ball milling), and collect the powder after ball milling.
[0086] The ball-milled powder was placed in a ceramic crucible, which was then placed in a tube furnace. Argon gas was introduced, and a heating program was set for pyrolysis (heating rate 5℃ / min, pyrolysis temperature 900℃, holding time 90min, followed by natural cooling). After the temperature dropped to room temperature, the pyrolyzed black powder was collected and placed in centrifuge tubes. Acetonitrile was added to the centrifuge tubes for soaking, followed by centrifugation. This soaking and centrifugation process was repeated three times. The resulting solid was washed with deionized water until neutral and then vacuum dried at 80℃ for 12h to obtain sulfur-nitrogen co-doped porous carbon nanosheets, named SN-cns-900.
[0087] The prepared catalyst was subjected to benzaldehyde oxidation-cyanation reaction. 0.5238 g benzaldehyde, 50 mg SN-cns-900, 200 μL ammonia water and 0.8 MPa oxygen were added to a 25 mL reaction vessel and reacted under magnetic stirring at a temperature of 80 °C for 8 h, yielding benzonitrile with a yield of 68.8%.
[0088] The results of Examples 1, 8, and 9 are shown in Table 5 and Appendix 6. Figure 8 As shown:
[0089] Table 5
[0090]
[0091] Example 10
[0092] Weigh out 4.5316g of sodium lignosulfonate, 3.0425g of chitosan, and 1.5027g of potassium hydroxide and mix them in a planetary ball mill (the planetary ball mill speed is 300rpm, and the ball milling is carried out intermittently in both forward and reverse directions for 12 hours. The interval between forward and reverse rotation is 5 minutes after every 30 minutes of ball milling). Collect the powder after ball milling.
[0093] The ball-milled powder was placed in a ceramic crucible, which was then placed in a tube furnace. Argon gas was introduced, and a heating program was set for pyrolysis (heating rate 5℃ / min, pyrolysis temperature 900℃, holding time 90min, followed by natural cooling). After the temperature dropped to room temperature, the pyrolyzed black powder was collected and placed in centrifuge tubes. Acetonitrile was added to the centrifuge tubes for soaking, followed by centrifugation. This soaking and centrifugation process was repeated three times. The resulting solid was washed with deionized water until neutral and then vacuum dried at 80℃ for 12h to obtain sulfur-nitrogen co-doped porous carbon nanosheets, named SN-cns-900.
[0094] The prepared catalyst was subjected to benzaldehyde oxidation-cyanation reaction. 0.5277 g benzaldehyde, 50 mg SN-cns-900, 200 μL ammonia water and 0.6 MPa oxygen were added to a 25 mL reaction vessel and reacted under magnetic stirring at a temperature of 80 °C for 8 h, yielding benzonitrile with a yield of 94.8%.
[0095] Example 11
[0096] Weigh out 4.5316g of sodium lignosulfonate, 3.0425g of chitosan, and 1.5027g of potassium hydroxide and mix them in a planetary ball mill (the planetary ball mill speed is 300rpm, and the ball milling is carried out intermittently in both forward and reverse directions for 12 hours. The interval between forward and reverse rotation is 5 minutes after every 30 minutes of ball milling). Collect the powder after ball milling.
[0097] The ball-milled powder was placed in a ceramic crucible, which was then placed in a tube furnace. Argon gas was introduced, and a heating program was set for pyrolysis (heating rate 5℃ / min, pyrolysis temperature 900℃, holding time 90min, followed by natural cooling). After the temperature dropped to room temperature, the pyrolyzed black powder was collected and placed in centrifuge tubes. Acetonitrile was added to the centrifuge tubes for soaking, followed by centrifugation. This soaking and centrifugation process was repeated three times. The resulting solid was washed with deionized water until neutral and then vacuum dried at 80℃ for 12h to obtain sulfur-nitrogen co-doped porous carbon nanosheets, named SN-cns-900.
[0098] The prepared catalyst was subjected to benzaldehyde oxidative cyanation reaction. 0.5312 g benzaldehyde, 50 mg SN-cns-900, 200 μL ammonia water and 1 MPa oxygen were added to a 25 mL reaction vessel and reacted under magnetic stirring at a temperature of 80 °C for 8 h to obtain benzonitrile with a yield of 95.5%.
[0099] The results of Examples 1, 10, and 11 are shown in Table 6 and Appendix 6 below. Figure 9 As shown:
[0100] Table 6
[0101]
[0102] Example 12
[0103] Weigh out 4.5178g of sodium lignosulfonate, 3.0111g of chitosan, and 1.4988g of potassium hydroxide and mix them in a planetary ball mill (the planetary ball mill speed is 400rpm, and the ball milling is carried out intermittently in both forward and reverse directions for 12 hours. The interval between forward and reverse rotation is 5 minutes after every 30 minutes of ball milling). Collect the powder after ball milling.
[0104] The ball-milled powder was placed in a ceramic crucible, which was then placed in a tube furnace. Argon gas was introduced, and a heating program was set for pyrolysis (heating rate 5℃ / min, pyrolysis temperature 900℃, holding time 90min, followed by natural cooling). After the temperature dropped to room temperature, the pyrolyzed black powder was collected and placed in centrifuge tubes. Acetonitrile was added to the centrifuge tubes for soaking, followed by centrifugation. This soaking and centrifugation process was repeated three times. The resulting solid was washed with deionized water until neutral and then vacuum dried at 80℃ for 12h to obtain sulfur-nitrogen co-doped porous carbon nanosheets, named SN-cns-900.
[0105] The prepared catalyst was subjected to benzaldehyde oxidative cyanation reaction. 0.5198 g benzaldehyde, 50 mg SN-cns-900, 200 μL ammonia water and 0.8 MPa oxygen were added to a 25 mL reaction vessel and reacted under magnetic stirring at a temperature of 80 °C for 8 h to obtain benzonitrile with a yield of 95.7%.
[0106] Example 13
[0107] Weigh out 4.5004g of sodium lignosulfonate, 3.1293g of chitosan, and 1.4896g of potassium hydroxide and mix them in a planetary ball mill (the planetary ball mill speed is 500rpm, and the ball milling is carried out intermittently in both forward and reverse directions for 12 hours. The interval between forward and reverse rotation is 5 minutes after every 30 minutes of ball milling). Collect the powder after ball milling.
[0108] The ball-milled powder was placed in a ceramic crucible, which was then placed in a tube furnace. Argon gas was introduced, and a heating program was set for pyrolysis (heating rate 5℃ / min, pyrolysis temperature 900℃, holding time 90min, followed by natural cooling). After the temperature dropped to room temperature, the pyrolyzed black powder was collected and placed in centrifuge tubes. Acetonitrile was added to the centrifuge tubes for soaking, followed by centrifugation. This soaking and centrifugation process was repeated three times. The resulting solid was washed with deionized water until neutral and then vacuum dried at 80℃ for 12h to obtain sulfur-nitrogen co-doped porous carbon nanosheets, named SN-cns-900.
[0109] The prepared catalyst was subjected to benzaldehyde oxidation-cyanation reaction. 0.5356 g benzaldehyde, 50 mg SN-cns-900, 200 μL ammonia water and 0.8 MPa oxygen were added to a 25 mL reaction vessel and reacted under magnetic stirring at a temperature of 80 °C for 8 h, yielding benzonitrile with a yield of 94.3%.
[0110] Example 14
[0111] Weigh out 4.5201g of sodium lignosulfonate, 3.1013g of chitosan, and 1.5159g of potassium hydroxide and mix them in a planetary ball mill (the planetary ball mill speed is 600rpm, and the ball milling is carried out intermittently in both forward and reverse directions for 12 hours. The intermittent direction is: pause for 5 minutes after every 30 minutes of ball milling), and collect the powder after ball milling.
[0112] The ball-milled powder was placed in a ceramic crucible, which was then placed in a tube furnace. Argon gas was introduced, and a heating program was set for pyrolysis (heating rate 5℃ / min, pyrolysis temperature 900℃, holding time 90min, followed by natural cooling). After the temperature dropped to room temperature, the pyrolyzed black powder was collected and placed in centrifuge tubes. Acetonitrile was added to the centrifuge tubes for soaking, followed by centrifugation. This soaking and centrifugation process was repeated three times. The resulting solid was washed with deionized water until neutral and then vacuum dried at 80℃ for 12h to obtain sulfur-nitrogen co-doped porous carbon nanosheets, named SN-cns-900.
[0113] The prepared catalyst was subjected to benzaldehyde oxidation-cyanation reaction. 0.5322 g benzaldehyde, 50 mg SN-cns-900, 200 μL ammonia water and 0.8 MPa oxygen were added to a 25 mL reaction vessel and reacted under magnetic stirring at a temperature of 80 °C for 8 h to obtain benzonitrile with a yield of 95.5%.
[0114] The results of Examples 1, 12-14 are shown in Table 7 and Appendix 1. Figure 10 As shown:
[0115] Table 7
[0116] Catalyst (calcination temperature) Reaction temperature / °C Ball mill speed / rpm Reaction time / h Ammonia dosage / μL Benzonitrile yield / % SN-cns-900 80 300 8 200 95.9 SN-cns-900 80 400 8 200 95.7 SN-cns-900 80 500 8 200 94.3 SN-cns-900 80 600 8 200 95.5
[0117] Example 15: Substrate Expansion
[0118] Weigh out 4.5316g of sodium lignosulfonate, 3.0425g of chitosan, and 1.5027g of potassium hydroxide and mix them in a planetary ball mill (the planetary ball mill speed is 300rpm, and the ball milling is carried out intermittently in both forward and reverse directions for 12 hours. The interval between forward and reverse rotation is 5 minutes after every 30 minutes of ball milling). Collect the powder after ball milling.
[0119] The ball-milled powder was placed in a ceramic crucible, which was then placed in a tube furnace. Argon gas was introduced, and a heating program was set for pyrolysis (heating rate 5℃ / min, pyrolysis temperature 900℃, holding time 90min, followed by natural cooling). After the temperature dropped to room temperature, the pyrolyzed black powder was collected and placed in centrifuge tubes. Acetonitrile was added to the centrifuge tubes for soaking, followed by centrifugation. This soaking and centrifugation process was repeated three times. The resulting solid was washed with deionized water until neutral and then vacuum dried at 80℃ for 12h to obtain sulfur-nitrogen co-doped porous carbon nanosheets, named SN-cns-900.
[0120] The prepared catalyst was subjected to an oxidative cyanidation reaction using benzaldehyde compounds. The reaction conditions were: 0.5 mmol substrate, 50 mg catalyst, 0.8 MPa O2, and 200 μL ammonia water. The reaction results are shown in Table 8 below.
[0121] Table 8
[0122] Serial Number Substrate product Temperature (°C) Time (h) Yield (%) 1 4-Methylbenzaldehyde 4-Methylbenzonitrile 80 8 95.6 2 4-Ethylbenzaldehyde 4-Ethylbenzonitrile 80 8 96.1 3 4-Hydroxybenzaldehyde 4-Hydroxybenzonitrile 80 8 91.5 4 4-Fluorobenzaldehyde 4-Fluorobenzonitrile 100 16 90.5 5 4-Chlorobenzaldehyde 4-Chlorobenzonitrile 100 16 93.8 6 4-Bromobenzaldehyde 4-Bromobenzonitrile 100 16 90.1 7 4-Methoxybenzaldehyde 4-Methoxybenzonitrile 80 8 94.9 8 4-Ethoxybenzaldehyde 4-Ethoxybenzonitrile 80 8 92.1 9 4-Isopropylbenzaldehyde 4-Isopropylbenzonitrile 80 8 92.4 10 3-Hydroxybenzaldehyde 3-Hydroxybenzonitrile 100 16 72.6
[0123] This invention prepares a catalyst by ball milling chitosan, sodium lignosulfonate, and potassium hydroxide followed by direct pyrolysis and calcination. The preparation method is simple, and the raw materials are environmentally friendly and sustainable. The prepared catalyst has high activity and high selectivity, and is easy to separate and reuse after the reaction. In addition to being metal-free, the catalyst also has the characteristics of non-leaching of active substances, heterogeneity, no further conversion of the formed nitriles, and good tolerance to other oxidizable groups, which proves that the catalyst has great potential.
[0124] The embodiments of the present invention have been described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and these variations still fall within the protection scope of the present invention.
Claims
1. A method for synthesizing nitrile from aldehyde, characterized in that, Includes the following steps: Aldehyde compounds and catalysts are added to a reaction vessel, acetonitrile is added as a solvent, and ammonia is added. Oxygen is first introduced to purge the air from the reaction vessel, and then a certain amount of oxygen is introduced. The reaction is carried out at 70-100℃ for 6-10 hours to obtain nitrile compounds. The catalyst is a non-metallic sulfur-nitrogen-doped porous carbon nanosheet, and the preparation method of the non-metallic sulfur-nitrogen-doped porous carbon nanosheet includes the following steps: Sodium lignosulfonate, chitosan, and potassium hydroxide were mixed and ball-milled. The powder was then placed in a tube furnace for pyrolysis. After pyrolysis, the powder was soaked in acetonitrile and centrifuged. The resulting solid was washed with deionized water and dried to obtain the non-metallic sulfur-nitrogen-doped porous carbon nanosheets.
2. The method for synthesizing nitrile from aldehydes according to claim 1, characterized in that, The mass ratio of sodium lignosulfonate, chitosan, and potassium hydroxide is (4-1):(2-1):
1.
3. The method for synthesizing nitrile from aldehydes according to claim 1, characterized in that, The ball mill rotates at 300-600 rpm and the milling time is 8-24 hours.
4. The method for synthesizing nitrile from aldehydes according to claim 1, characterized in that, The pyrolysis conditions are as follows: under an inert gas atmosphere, the heating rate is 4-6℃ / min, the pyrolysis temperature is 600-900℃, the holding time is 60-90min, and finally the temperature is allowed to drop naturally.
5. The method for synthesizing nitrile from aldehydes according to claim 1, characterized in that, The aldehyde compounds include at least one of benzaldehyde, 4-methylbenzaldehyde, 4-ethylbenzaldehyde, 4-hydroxybenzaldehyde, 4-fluorobenzaldehyde, 4-bromobenzaldehyde, 4-chlorobenzaldehyde, 4-nitrobenzaldehyde, 4-methoxybenzaldehyde, 4-isopropylbenzaldehyde, 4-ethoxybenzaldehyde, and 3-hydroxybenzaldehyde.
6. The method for synthesizing nitrile from aldehydes according to claim 1, characterized in that, The mass-to-volume ratio of the aldehyde compound to ammonia is 1 g: (0.05-0.5) mL.
7. The method for synthesizing nitrile from aldehydes according to claim 1, characterized in that, The oxygen flow rate is such that the final pressure inside the reactor after oxygen flow is 0.5-1 MPa.
Citation Information
Patent Citations
Synthetic method for p-tolunitrile
CN110526828A
Preparation method of supported cobalt-based catalyst and application of supported cobalt-based catalyst in synthesis of nitrile from alcohol
CN114042461A
Preparation method and application of lignin-based hierarchical-pore carbon material
CN106082211A
Preparation method of sodium lignin sulfonate / chitosan high-mesoporous nitrogen and sulfur co-doped porous carbon-based supercapacitor electrode material
CN117012557A
